Rapid parallel acquisition of somatic mutations after NPM1 in acute myeloid leukaemia evolution - Grove, C; Bolli, N; Manes, N; Varela, I; Van't Veer, M; Bench, A; Eldaly, H; Wedge, D; Van Loo, P; Vassiliou, G (Wiley, 2016)
The steps in the progression from subclinical clonal haemopoiesis to acute myeloid leukaemia (AML) have not been defined, nor has its likelihood or latency. NPM1 mutations were not found to drive clonal haemopoiesis in haematologically normal individuals(Genovese et al, 2014; Jaiswal et al, 2014; Xie et al, 2014; McKerrell et al, 2015), highlighting their strong leukaemogenic pedigree, but making them difficult to capture at a stage prior to frank AML. As occasional cases of NPM1-mutated myelodysplastic syndrome/myeloproliferative neoplasm have been described(Caudill et al, 2006; Peng et al, 2016), we hypothesised that detailed analysis of such cases could offer insights into leukaemic evolution after the acquisition of NPM1 mutations. Here, we describe the genetic events driving rapid progression of a case of NPM1 mutant chronic myelomonocytic leukaemia (CMML) to full-blown AML.